2005
DOI: 10.1097/01.mpa.0000168222.05591.a0
|View full text |Cite
|
Sign up to set email alerts
|

Differential and Synergistic Effects of Platelet-derived Growth Factor-BB and Transforming Growth Factor-??1 on Activated Pancreatic Stellate Cells

Abstract: PDGF-BB augments effects of TGF-beta1 on the mRNA level presumably because of up-regulation of TGF-beta1 synthesis and common signaling pathways of the 2 cytokines. However, at the protein level, PDGF-BB impairs typical TGF-beta1 effects such as increased synthesis of collagen (type I) and alpha-SMA. Moreover, PDGF-BB facilitates degradation of extracellular matrix proteins by enhancement of MMP synthesis, but MMP activity was probably limited because of elevated tissue inhibitor of metalloproteinase 1 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 43 publications
3
27
0
Order By: Relevance
“…A direct fibrogenic effect of CCK could be an important mediator of pancreatic fibrosis, suggesting that CCK receptors could be an interesting therapeutic target in patients with chronic pancreatitis. To date, the cytokine TGF-␤ had been the most potent stimulator of collagen synthesis in PSC (35). As shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A direct fibrogenic effect of CCK could be an important mediator of pancreatic fibrosis, suggesting that CCK receptors could be an interesting therapeutic target in patients with chronic pancreatitis. To date, the cytokine TGF-␤ had been the most potent stimulator of collagen synthesis in PSC (35). As shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to TGF-␤, and in contrast to other cytokines like PDGF (35), both CCK and gastrin inhibited proliferation. As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting finding presented here is the strong positive correlation between serum PDGF-BB and TGF-β1 concentrations in patients with CP. In vitro studies showed that PDGF-BB causes upregulation of TGF-β1 synthesis in pancreatic stellate cells [6]. Therefore, it cannot be ruled out that PDGF-BB stimulates TGF-β1 synthesis in CP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies postulated that myofibroblasts (transformed pancreatic stellate cells) and profibrotic cytokines such as platelet-derived growth factor-BB (PDGF-BB) and transforming growth factor-β1 (TGF-β1) play an important role in pancreatic fibrosis [1,2,3,4,5,6,7,8,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%